MieliLiike-malli mielenterveyden edistämisen työkaluna 16– 29-vuotiailla nuorilla: terveydenhuollon ja liikunta-alan ammattilaisten näkemyksiä MieliLiike-mallista ja sen soveltuvuudesta käytännön asiakastyöhön - Lindfors, Roosa; Forsman, Inga (2025)
Forsman, I & Lindfors, R. 2025. MieliLiike-model as a Tool for Promoting Mental Health in youth aged 16–29: Views of health and sports professionals on the MieliLiike-model and its suitability for practical client work. Faculty of Sport and Health Sciences, University of Jyväskylä, master’s thesis, 69 pp, 3 appendices.